Mutation Changes in the preC/Core Promoter in HBeAg-Positive Patients With Chronic Hepatitis B During Interferon Therapy. Issue 5 (February 2016) - Geng, Yan; Wang, Xiangling; Lu, Xiaolan; Wu, Xiaokang; Xu, Nan; Han, Lei; Xu, Jiru
Abstract : Abstract: To study the changes in 3 mutations related with hepatitis B e antigen (HBeAg) in patients with HBeAg-positive chronic hepatitis B (CHB) during interferon therapy. HBeAg seroconversion is a major therapeutic milestone for patients with HBeAg-positive CHB. The precore mutation G1896A and the basal core promoter mutations A1762T/G1764A are 3 important mutations that affect the expression of HBeAg; however, the change of these 3 mutations in CHB patients during interferon therapy has not yet been evaluated. Sixty-four treatment-naive patients with HBeAg-positive CHB were treated with interferon for 48 weeks and followed up for 24 weeks. Serum samples were collected from all of the participants at different time points and then subjected to viral DNA extraction. The precore and basal core promoter sequences were determined using nested PCR and direct sequencing. The treatment outcomes were confirmed both at the end of therapy and the follow-up period, and the results were compared between patients with mutant and wild-type virus. No significant difference in HBeAg loss and HBeAg seroconversion was observed between patients with mutant versus wild-type virus although the portion of patients who achieved HBeAg loss/seroconversion with mutant virus was a little higher than in patients with wild-type virus. Once a mutation exists, it is not replaced with the wild-type sequence during interferon therapy and follow-up; moreover, our results show that mutants stably coexist with the wild-type virus during interferon therapy. This study shows the changes in 3 mutations affecting the expression of HBeAg during interferon therapy. However, additional studies with a larger sample size and more sensitive detection methods are needed to uncover the underlying mechanism and clinical significance of these results.